(3GSS GdGbQGV GdRQGYi hGdJehjd GdJYGhfi (B/s - (3aGQS, Ydj eMehOs ((3GdHjVGA(B: s (3LGeYI YeQ GdeNJGQ(B, s, 2005)
(3GgejI GdGbQGV GdRQGYj aj GdOhd GdfGejI h GgejI QGS GdeGd aj GdYed GdeRQYj GVGaI Gdi GdGOGQI GdeGdjI GdeRQYjI h cPG eUGOQ GdGbQGV GdRQGYj(B, (3JUfja GdbQhV GdRQGYjI(B, (3VeGfGJ GdbQhV GdRQGYjI(B, (3GOGQI GdbQhV GdRQGYjI cPdc GdGLQGAGJ GdGOGQjI dWdH GdbQhV GdRQGYjI(B, (3JcGdja GdbQhV h GdaGFOI GdHSjWI(B, (3GdaGFOI GdeQcHI(B, (3MSGHGJ GSJgdGc GdbQhV(B, (3JSOjO GdbQhV GdRQGYjI h GdcaGAI GdJMUjdjI h GdJehjd GdJYGhfj(B, (3GdGTQGa h GdeQGbHI Ydi GdbQhV GdRQGYjI h GdYdGbI GdJcGedjI Hjf GdGbQGV GdRQGYj h GdNOeGJ GdRQGYjI GdGNQi GVGaI Gdi GSS fLGM HQGeL GdGbQGV GdRQGYj h GdJehjd GdJYGhfj h RjGOI aYGdjJgG(B, (3GdJGejf h GdGfTWI GdRQGYjI h GNjQG GdJehjd aj GdeUGQa ZjQ GdQHhjI (B((3GdGSdGejI(B).s
(3eQGLY U(B.495, (3edGMb U(B.471s
Keywords: (3GdGbQGV GdRQGYjs; (3GdRQGYI (B- (3Jehjds